2014
DOI: 10.1186/1475-2840-13-45
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds of various glycemic measures for diagnosing diabetes based on prevalence of retinopathy in community-dwelling Japanese subjects: the Hisayama Study

Abstract: BackgroundThere has been controversy over the diagnostic thresholds of hemoglobin A1c (HbA1c) for diabetes. In addition, no study has examined the thresholds of glycated albumin (GA) and 1,5-anhydroglucitol (1,5-AG) for diagnosing diabetes using the presence of diabetic retinopathy (DR). We examined the optimal thresholds of various glycemic measures for diagnosing diabetes based on the prevalence of DR in community-dwelling Japanese subjects.MethodsA total of 2,681 subjects aged 40-79 years underwent a 75-g o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 47 publications
6
28
0
Order By: Relevance
“…Particularly, the cutoff of FPG by deciles in the Chinese population (7.03–7.2 mmol/L) was much higher than those in other Asian populations (6.2–6.5 mmol/L) [13, 15, 16, 23, 24]. However, in our study, the optimal FPG, determined using ROC curve analysis (6.52 mmol/L), was close to that in the previous Asian studies.…”
Section: Discussionsupporting
confidence: 76%
“…Particularly, the cutoff of FPG by deciles in the Chinese population (7.03–7.2 mmol/L) was much higher than those in other Asian populations (6.2–6.5 mmol/L) [13, 15, 16, 23, 24]. However, in our study, the optimal FPG, determined using ROC curve analysis (6.52 mmol/L), was close to that in the previous Asian studies.…”
Section: Discussionsupporting
confidence: 76%
“…1,5-AG reflects glucose control over the previous 48 h to 2 weeks, its concentration is mainly useful in detecting postprandial glucose (PPG), where lower levels result from glucose peaks above the renal threshold and particularly useful in patients with A1C <8%. 49 1,5-AG was found to be negatively associated with longterm risk of microvascular outcomes, 14,50,51 and an increased risk of CV disease [52][53][54] and mortality in DM. 53 The concentrations of 1,5-AG decrease as pregnancy progresses in both nondiabetic and diabetic subjects 55 ; nonetheless, 1,5-AG has been found to be a useful marker in pregnancy complicated by DM, associated with mean glycemia, glycemic variability (GV), and glycemic exposure in females with T1D1 in whom glycemic control was assessed by a continuous glucose monitoring (CGM) system.…”
Section: Glycated Proteinsmentioning
confidence: 93%
“…FA refers to several proteins, with albumin accounting for *90%; GA refers exclusively to albumin. 12 Glycated proteins have been associated with micro- [13][14][15] and macrovascular complications [16][17][18][19][20][21] and mortality in people with DM. 22 Several prospective studies have shown their utility for patients at risk of developing micro-and macrovascular complications.…”
Section: Glycated Proteinsmentioning
confidence: 99%
“…29 In a Japanese cohort of more than 2,500 participants, the performance of glycated albumin and 1,5-AG to identify cases of retinopathy—as measured by the C-statistic—was shown to be comparable to fasting glucose and HbA1c. 38 In a study of 1,575 Japanese adults without diagnosed diabetes, glycated albumin was associated with carotid artery intima-media thickness, a measure of subclinical atherosclerosis. 39 Glycated albumin has been associated with prevalent kidney outcomes, 4042 and cardiovascular disease.…”
Section: Associations Of Nontraditional Markers Of Hyperglycemia Withmentioning
confidence: 99%